Análise da gestão dos recursos do ICMS Verde: um estudo de caso no município de Monte Alegre - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The general objective of this work is to understand how the municipality of Monte Alegre manages the resources received from the Tax on the Circulation of Green Goods and Services. Secondary, its specific objectives are: to present a conceptual theoretical review of Payments for Environmental Services, to descriptively show the functioning of the PES instrument called ICMS Verde in the State of Pará and to identify possibilities for improvements in the management of resources received via ICMS Verde by the municipality. from Monte Alegre. From a methodological point of view, the work used a qualitative approach using public documents, articles and scientific works, booklets, decrees, laws and interviews with key actors in the ICMS Verde management process in Monte Alegre as data and information collection instruments. . The research results indicated that, although the ICMS Verde policy is an innovative Payments for Environmental Services initiative with good results in several Brazilian states, its practical implementation in the State of Pará still requires adjustments. In the case of Monte Alegre, it is observed that as the municipality has a vast rural area, it allows the capture of significant resources via ICMS Verde. However, the form of management carried out by the municipality is still precarious, and it was only in 2016 that the municipality implemented its Municipal Environmental Council and managed to separate the resources received from ICMS Verde from other sources received by the City Hall. Thus, in 2024 the first Notice was launched to cover organizations with resources raised via ICMS Verde.
Keywords: Serviços ambientais; Gestão municipal; ICMS Verde; Monte Alegre; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS